HUBUNGAN POLA ASUH IBU DENGAN KEJADIAN STUNTING PADA BALITA USIA 12-59 BULAN DI PUSKESMAS AMUNG BARAT - br Ginting, Berlianta; Sri Purwanti, Anik (NHM PRESS, 2024)
Background: Stunting is a significant health problem in Indonesia and has a long-term impact on children's physical and cognitive development. Mother's parenting style plays an important role in the growth and development of toddlers. Objective: This study aims to analyze the relationship between maternal parenting patterns and the incidence of stunting in toddlers aged 12-59 months at the West Amung Health Center. Method: This study used a cross-sectional design with a sample of 16 toddlers selected using purposive sampling. Data was collected through questionnaires regarding maternal parenting patterns and anthropometric measurements to determine stunting status in toddlers. Data analysis was carried out using the chi-square test to determine the relationship between maternal parenting variables and the incidence of stunting. Results: Of the 16 toddlers studied, 62.5% of them experienced stunting. The results of the analysis show that there is a significant relationship between maternal parenting patterns and the incidence of stunting in toddlers (p < 0.05). Mothers who implement good parenting patterns, including providing adequate food, optimal health care, and adequate psychosocial stimulation, have children with better nutritional status. Conclusion: This study concludes that maternal parenting styles are significantly related to the incidence of stunting in toddlers at the West Amung Community Health Center. Interventions that focus on increasing maternal knowledge and parenting practices can be an effective strategy to reduce the prevalence of stunting in this region. Further research with a larger sample size and more diverse variables is recommended to strengthen these findings.